Mechanism and microstructure evolution of high temperature oxidation of end-of-life NdFeB rare earth permanent magnets. (15th April 2021) - Nababan, Deddy C.; Mukhlis, Reiza; Durandet, Yvonne; Pownceby, Mark I.; Prentice, Leon; Rhamdhani, M Akbar
Highlights: The microstructure and oxidation mechanism of EOL NdFeB magnet at 973−1473 K were investigated. Four distinct oxidation microstructure evolutions were observed at different temperature range. The coating on the magnet was found to affect the oxidation mechanism and microstructure evolution. The distinct oxide morphologies have implications for strategies for the recycling process. Abstract: The behaviour of rare earth permanent magnets during oxidation profoundly determines the high temperature recycling processes. This current study analysed the microstructure evolution of end-of-life, coated NdFeB rare earth permanent magnets after oxidization at 973−1473 K under ambient air conditions. Four distinct categories of microstructure evolution were observed at the temperatures of 973 K, 1073 K, 1173−1273 K, and 1373−1473 K. The presence of a Ni/Cu/Ni coating was found to significantly affect the oxidation mechanism. The distinct oxide morphologies developed at these temperatures have different implications for designing strategies for the recycling process.